The Effect of Guided Discovery Based Interactive E-Worksheet on Students' Analytical Thinking Ability - Puspitasari, Santi (Jurnal Pengajaran MIPA, 2020)
An interactive e-worksheet is an alternative that teachers can design themselves to support the development of higher order thinking skills in students, including analytical thinking skills. One learning model that can support the development of analytical thinking skills is guided discovery. This study aims to determine the effect of interactive e-worksheets based on guided discovery on students' analytical thinking skills. This type of research is a pre-experimental study using a one group pretest posttest research design. The research subjects were students of class X SMAN 1 Parongpong. The instrument used includes tests of students' analytical thinking skills. The results of the study in the form of the Wilcoxon test (Asym sig 2 tailed 0.001 0.05) showed that there was a significant effect on changes in students' analytical thinking skills with an increase in the average score (gain score) of 27.3 after the implementation of the e-worksheet. The student response to the e-worksheet was considered good, with several obstacles such as a bad internet connection.